Fischernolides A–D, four novel diterpene-based meroterpenoid scaffolds with antitumor activities from Euphorbia fischeriana. Issue 14 (22nd February 2019) - Zhang, Jia; He, Jun; Cheng, Yung-Chi; Zhang, Pei-Cheng; Yan, Yu; Zhang, Hao-Jun; Zhang, Wei-Ku; Xu, Jie-Kun
Abstract : Fischernolides A–D (1–4 ), representing the rare 28-carbon meroterpenoid skeleton of abietane and an acylphloroglucinol conjugate, bearing an α-furanone or α-pyrone ring, were isolated and identified from the roots of Euphorbia fischeriana . Abstract : Fischernolides A–D (1–4 ), four meroterpenoids based on diterpene and acylphloroglucinol, possessing an unprecedented 28-carbon skeleton with a novel scaffold, were isolated from the roots of Euphorbia fischeriana . Their structures and absolute configurations were determined by comprehensive chemical analyses including spectroscopic techniques, electronic circular dichroism (ECD) spectroscopy, and single crystal X-ray diffraction experiments. The possible biogenetic pathway to generate1–4 through aldol condensation was also proposed. Compound2 showed significant cytotoxicity and can induce the apoptosis of MCF-7 and Bel-7402 cell lines by caspase activation.